‘Loaded’: indie guitar rock, canonism, white masculinities - Bannister, Matthew (Popular Music, 2006)
Indie alternative rock in the 1980s is often presented as authentically autonomous, produced in local scenes, uncaptured by ideology, free of commercial pressures, but also of high culture elitism. In claiming that the music is avant-garde, postmodern and subversive, such accounts simplify indie's historical, social and cultural context. Indie did not simply arise organically out of developing postpunk music networks, but was shaped by media, and was not just collective, but also stratified, hierarchical and traditional. Canon (articulated through practices of archivalism and connoisseurship) is a key means of stratification within indie scenes, produced by and serving particular social and cultural needs for dominant social groups (journalists, scenemakers, tastemakers, etc.). These groups and individuals were mainly masculine, and thus gender in indie scenes is an important means for deconstructing the discourse of indie independence. I suggest re-envisioning indie as a history of record collectors, emphasising the importance of rock ‘tradition’, of male rock ‘intellectuals’, second-hand record shops, and of an alternative canon as a form of pedagogy. I also consider such activities as models of rational organisation and points of symbolic identification.
Publisher: Cambridge University Press

The Study of Gender in Culture - Cragin, Becca; Simonds, Wendy (Handbook of the Sociology of Gender, 2006)
Keywords: Critical Dialogue; Cultural Study; Feminist Study; Popular Culture; Soap Opera

Sexism and misogyny in American hip-hop culture - Larsen, Jane Kathrine (2006)
The proliferation of hip-hop culture today is so great that we may speak of a modern-day pop-cultural phenomenon. This phenomenon has found its way from the ghetto areas in the Bronx to white suburbia in the U.S. and Europe over the last thirty years. The specific subject for my study is the overt sexism that is present in this culture. Sexism can take on a variety of forms and expressions, as there are various degrees and definitions of this concept. Hence, my aim is to locate some of these definitions and relate them to hip-hop’s expression. The development from a black sub-culture to an immensely successful genre in music is of great interest to my study, in terms of hip-hop as a pop-cultural and sociological phenomenon. There are also cultural, gender, and racial concerns to be considered in this respect, and my account of these includes an exploration of the time and place for the birth and development of hip-hop. The extent of sexism, and even outright misogyny, in hip-hop today is so pervasive, that protests have started to come from every direction of America’s pop-cultural, feminist, and academic sphere. The sociological and pop-cultural factors that are present in this discussion, is related to the topic of gender roles and relationships in African American culture. In my discussion on the hip-hop industry’s responsibility for distributing these negative depictions of women in hip-hop videos and lyrics, I have included some examples from studies that focus on the racial stereotypes in connection to gangsta-rap. The concept of image and authenticity is important in this respect, and there is a level of deliberate marketing strategies behind the lifestyle-oriented aliases of the rap artists. Since hip-hop and rap music traditionally have been overwhelmingly masculine expressions, it is necessary to take a look at the role of female artists within the hip-hop community. In this respect, I find that women have traditionally been rejected or hindered to participate in hip-hop’s brotherhood. Women in hip-hop have thus either tried to make careers for themselves, or adapt into the mass-marketed and male-defined stereotype that in many ways relate to the sexist images that are currently so pervasive. The sexist attitudes represent a point of view that I believe is derived from popularised representations in the media. These representations tally well with the already existing prejudiced opinions that have been created in terms of race discrimination and patriarchal values. Part of the problem with these representations is the lack of alternative images. If there are no counter-images that will speak against the existing sexist depictions, then there will be no progress in terms of addressing sexism directly. The constructed images of African Americans that the media are chiefly responsible for distributing, are what many non-black citizens believe to be the truth about black people. As long as people do not interact socially across ethnic borders, these representations will continue to circulate. In hip-hop culture, this is still ubiquitous in terms of the stereotyping of race. An interesting, and perhaps surprising aspect to some, is the fact that most of hip-hop’s buying audience is white. The negative stereotyping in hip-hop which was initiated by the gangsta-era, was displayed mainly by African American men who acted as criminal gangsters (hence the name), and who lived up to their role as “bad”, thus confirming the stereotyped conception that many non-blacks had of black people. The badness is then articulated within hip-hop’s boundaries through violence and as a glorification of the “thug life” by the men, whereas for women it is commonly expressed as commodified sexuality. Contemporary hip-hop resembles the minstrel shows of the 19th century in this respect, where working class white men dressed up as plantation slaves.
Accepted: 2013-03-12T11:40:46Z
Keywords: Hip-hop culture; Myriam; Perfoming arts